Extensive mutagenesis experiments corroborate a structural model for the DNA deaminase domain of APOBEC3G - Chen, Kuan-Ming (2007)
APOBEC3G is a single-strand DNA cytosine deaminase capable of blocking retrovirus and retrotransposon replication. APOBEC3G has two conserved zinc-coordinating motifs but only one is required for catalysis. Here, deletion analyses revealed that the minimal catalytic domain consists of residues 198-384. Size exclusion assays indicated that this protein is monomeric. Many (31/69) alanine substitution derivatives of APOBEC3G198-384 retained significant to full levels of activity. These data corroborated an APOBEC2-based structural model for the catalytic domain of APOBEC3G indicating that most non-essential residues are solvent accessible and most essential residues cluster within the protein core.